Manganese-oxidizing Exiguobacterium acetylicum 4-3-1 reduces cadmium accumulation in spinach - Sun, Yujia; Ding, Mengyao; Zheng, Wenjuan; Zhang, Haoran; Lu, Zhenkun; Zhang, Jian; Zhao, Guoyan (Frontiers in Microbiology, 2026)
Cadmium (Cd) accumulation in edible plants is a significant global concern. This research explores the potential of a manganese-oxidizing rhizobacterium, Exiguobacterium acetylicum 4-3-1, to promote spinach growth while reducing Cd uptake. The bacterium produces indole-3-acetic acid and siderophores and effectively removed 73.74% of free CdCl2. Under Cd stress (10.5 mg/kg), E. acetylicum 4-3-1 significantly increased spinach biomass by 184.3% (dry weight) and chlorophyll content by 33.99%, while decreasing the Cd concentration in spinach leaves by 53.07% through both intrinsic and extrinsic mechanisms. Intrinsically, E. acetylicum 4-3-1 inoculation up-regulated pathways related to photosynthesis and energy metabolism in spinach, while down-regulating genes linked to heavy metal transport. Extrinsically, it oxidizes Mn(II) to form manganese oxides that may immobilize Cd. Moreover, inoculation with strain 4-3-1 altered the rhizosphere microbiome of spinach, increasing the presence of beneficial bacteria like Bacillales. A synthetic community (SynCom) composed of Bacillus subtilis and E. acetylicum 4-3-1 demonstrated synergistic effects on spinach growth under Cd stress. Thus, E. acetylicum 4-3-1 has the potential for Cd bioremediation in crops and promotes sustainable agriculture.